2002
DOI: 10.1177/1473325002001003645
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Perceptions and Attitudes of Staff Working in Community Based Children's Homes: Are Their Needs Being Met?

Abstract: There remains considerable ambiguity and negativity around the purpose and effectiveness of children's homes. High levels of unqualified staff, low status and poor pay and conditions have continued to be the norm within residential child care. In light of this situation it is appropriate to ask why staff are viewed as a key ingredient in the service provision. It is particularly significant given the views of staff and the tasks they undertake have not been widely researched. This article provides a summary of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Research has shown that caregivers working in big orphanages have high levels of stress, anxiety, depression, and job dissatisfaction, but this finding does not hold true for those working in smaller homes (Heron & Chakrabarti, 2002). One possibility for this difference may be that in smaller homes there is a chance to establish affectional bonds with children and have a rewarding experience, but this has not been studied.…”
Section: "Getting Involved": a Thematic Analysis Of Caregivers' Perspmentioning
confidence: 99%
“…Research has shown that caregivers working in big orphanages have high levels of stress, anxiety, depression, and job dissatisfaction, but this finding does not hold true for those working in smaller homes (Heron & Chakrabarti, 2002). One possibility for this difference may be that in smaller homes there is a chance to establish affectional bonds with children and have a rewarding experience, but this has not been studied.…”
Section: "Getting Involved": a Thematic Analysis Of Caregivers' Perspmentioning
confidence: 99%
“…Practitioners have reported suffering from feelings of fear, anger and impotence (Knorth et al, 2007) and being unable to deal effectively with the behaviour and needs of people in their care (Heron and Chakrabarti, 2002a).…”
Section: Education As a Transitionmentioning
confidence: 99%
“…Very little is known about factors that contribute to the quality of caregiving practices in institutional settings (Heron & Chakrabarti, 2002). Caregiving professions in general have been described as experiencing a high degree of stress (Kahn, 2005).…”
Section: Research On Institutional Rearingmentioning
confidence: 99%